University as an Environment of Innovative Interactions - A. V. Kiryakova; N. A. Kargapoltseva; I. D. Belonovskaya; S. A. Duzhnikov (Высшее образование в России)
Orenburg State University is presented as an environment of multilevel multidimensional interaction of various subjects. The dynamics of value interaction between students and teachers is revealed. In the conditions of modern social and digital transformations, the nature of joint activity is changing from formal-reproductive to value-creative. It is pointed out that the dominant instrumental values of students are shifting due to the information and technological features of distance educational technologies. Youth interactions and socio-cultural practices are integrated into the comprehensive program for the development of the OSU socio-cultural environment on the basis of various project activities. The implementation of the program is characterized by receiving grant support for student initiatives. International aspects of university interaction are represented by the development of forms of scientific and educational export to universities of the Republic of Kazakhstan.